Analisis Pembagian Waris Sistem Adat dalam Perspektif Keadilan Gender - Makagiansar, San Frans; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Customary inheritance systems in Indonesia are divided into three types: patrilineal, matrilineal, and bilateral, each providing different treatment of women’s inheritance rights. This research examines inheritance distribution in customary systems from a gender justice perspective, focusing on women’s inheritance rights regulation, factors causing gender inequality, and efforts to achieve justice through court decisions and socio-cultural change. Using a descriptive-analytical normative juridical approach, this research examines laws and regulations, Supreme Court decisions, and related academic studies. The findings indicate that in the patrilineal system, women tend to be marginalized and do not receive equal inheritance rights. Conversely, in the matrilineal system, women become the primary heirs, yet this system faces tension with Islamic law which adheres to bilateral principles. The bilateral system is considered more open as it does not differentiate inheritance rights between men and women. Gender inequality is caused by strong patriarchal culture, tension between customary and religious law, and resistance to social change. Various efforts have been made through Supreme Court jurisprudence such as Decision 179 K/SIP/1961, Decision 147 K/Pdt/2017, and Jurisprudence 3/Yur/Pdt/2018, as well as acculturation between Islamic law and customary law that encourages shifts toward a fairer inheritance system. This research recommends strengthening jurisprudence, harmonizing laws, and increasing public awareness of gender justice in inheritance.